What makes for good and bad neighbours? An emerging research agenda in the study of Chinese environmental politics. Issue 5 (3rd September 2018) - Eaton, Sarah; Kostka, Genia
ABSTRACT: Tackling China's grave environmental problems increasingly turns on questions of sub-national interjurisdictional relations. What are the conditions under which neighbouring localities cooperate in stewardship of the natural environment? What factors give rise to interjurisdictional conflict such as pollution spillovers? Through a combination of empirical and theoretical reflections, a research agenda to better understand these issues is outlined. First, China's recent innovative approaches to the promotion of interjurisdictional cooperation are examined. An in-depth case study of interjurisdictional ecological protection 'redline' zones underscores the difficulties of inculcating environmental neighbourliness between local governments. Yet, a precise diagnosis of the problem remains elusive because too little is known about the underlying drivers of interjurisdictional relations in China. An analytical framework that draws insight from contemporary China studies and comparative environmental governance scholarship is offered for the study of interjurisdictional environmental relations in China.